2023
DOI: 10.1038/s41598-023-33810-y
|View full text |Cite
|
Sign up to set email alerts
|

Impairments following COVID-19 infection: manifestations and investigations of related factors

Abstract: The COVID-19 pandemic had a major global impact on the health and wellbeing for many individuals. Even though the infection rates have gone down due to the availability of vaccines, the consequences of the disease are still present due to persistent symptoms among individuals. The aim of the current study was to map long‐term impairments in individuals infected with COVID-19 by applying the framework of the World Health Organization’s International Classification of Functioning, Disability and Health (ICF) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The third possible explanation for these ndings is sustained recovery of COVID-19-related persistent symptoms over time. A substantial proportion of individuals infected with COVID-19 reports experiencing at least one moderate-to-severe impairment due to COVID-19 infection, with fatigue being the most commonly reported symptom [17,52,53,54,55,56,57,58,59,60]. Furthermore, our previous cross-sectional study revealed that post-COVID impairments and fatigue emerged as signi cant predictors of mental ill-health in individuals who were infected with COVID-19 infection [10].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The third possible explanation for these ndings is sustained recovery of COVID-19-related persistent symptoms over time. A substantial proportion of individuals infected with COVID-19 reports experiencing at least one moderate-to-severe impairment due to COVID-19 infection, with fatigue being the most commonly reported symptom [17,52,53,54,55,56,57,58,59,60]. Furthermore, our previous cross-sectional study revealed that post-COVID impairments and fatigue emerged as signi cant predictors of mental ill-health in individuals who were infected with COVID-19 infection [10].…”
Section: Discussionmentioning
confidence: 91%
“…The initial increase in insomnia could be attributed to the physiological and psychological effects of the acute phase of COVID-19 infection and the side effects of COVID-19-related medications which disrupted sleep quality and quantity during the early stages of recovery and increased the risk of developing chronic insomnia later after recovery [54,66,67,68]. Second, sleep-related problems were reported as one of the most common remaining symptoms experienced after recovering from COVID-19 [17,48] Additionally, it has been shown to contribute to higher levels of mental ill-health following COVID-19 infection [10]. Therefore, it is reasonable to conclude that individuals who experienced severe COVID-19 infection in the acute phase continue to be at risk for mental ill-health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations